(untitled) (Journal of Human Sciences, 2021)
The study aims to demonstrate the role of kindergartens in developing the values of moral and social education among pre-school children from the point of view of mothers. A random sample was selected from (60) mothers. They were randomly selected, using the descriptive and analytical approach. After making sure of the validity and consistency study tool, the study research questions were answered through the use of appropriate statistical methods. The results of the study showed the following: The role of kindergartens, from mothers’ point of view in developing the moral and social values of children, has come to a high degree. The current study did not find statistically significant differences in the role of kindergartens in the development of moral and social values due to the variable of age, gender of the child, the age of the mother, and her educational qualification. The study found statistically significant differences in the role of kindergartens in developing moral values from the point of view of mothers.